Evolutionary dynamics of Enterococcus faecium reveals complex genomic relationships between isolates with independent emergence of vancomycin resistance. Issue 1 (19th January 2016) - van Hal, Sebastiaan J.; Ip, Camilla L. C.; Ansari, M. Azim; Wilson, Daniel J.; Espedido, Bjorn A.; Jensen, Slade O.; Bowden, Rory
Abstract : Enterococcus faecium, a major cause of hospital-acquired infections, remains problematic because of its propensity to acquire resistance to vancomycin, which currently is considered first-line therapy. Here, we assess the evolution and resistance acquisition dynamics of E. faecium in a clinical context using a series of 132 bloodstream infection isolates from a single hospital. All isolates, of which 49 (37 %) were vancomycin-resistant, underwent whole-genome sequencing. E. faecium was found to be subject to high rates of recombination with little evidence of sequence importation from outside the local E. faecium population. Apart from disrupting phylogenetic reconstruction, recombination was frequent enough to invalidate MLST typing in the identification of clonal expansion and transmission events, suggesting that, where available, whole-genome sequencing should be used in tracing the epidemiology of E. faecium nosocomial infections and establishing routes of transmission. Several forms of the Tn 1549 -like element– vanB gene cluster, which was exclusively responsible for vancomycin resistance, appeared and spread within the hospital during the study period. Several transposon gains and losses and instances of in situ evolution were inferred and, although usually chromosomal, the resistance element was also observed on a plasmid background. There was qualitative evidence for clonal expansions of both vancomycin-resistant and vancomycin-susceptible E. faecium with evidence of hospital-specific subclonal expansion. Our data are consistent with continuing evolution of this established hospital pathogen and confirm hospital vancomycin-susceptible and vancomycin-resistant E. faecium patient transmission events, underlining the need for careful consideration before modifying current E. faecium infection control strategies.